Software development for people with intellectual or developmental disabilities in 2010–2019 : a systematic mapping study - Kasanen, Mari (2020)
People with intellectual or developmental disabilities (IDD) may need software applications that are specifically developed to answer the requirements their disabilities pose. Article 9 of the 2006 Convention on the Rights of Persons with Disabilities of the United Nations, which concerns accessibility, summarizes the motivation of this study. This thesis conducted a systematic mapping study of applications for people with IDD that were published as journal articles or conference papers in 2010–2019. There were 98 accepted articles. Key findings include a rising, yet small, amount of literature through the decade. The intended users most popularly are children and have either Autism spectrum disorder or an intellectual disability. Nearly half of the applications had a connection to mobile technology.